2008
DOI: 10.4028/www.scientific.net/msf.587-588.534
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Crystallization Kinetics on the Microstructural Properties of γ-PVDF

Abstract: The kinetics of the isothermal crystallization of the γ-phase Poly(vinylidene fluoride) has been investigated. Samples were prepared from the melt at different crystallisation temperatures and the variation of the microstructure of the samples was monitored with time by optical microscopy. Raman and Infrared transmission spectroscopies also show the appearance of the γ-phase for higher crystallisation temperatures. Two types of γ-phase spherulites have been identified. These spherulites represents different wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
(8 reference statements)
0
8
0
Order By: Relevance
“…Briefly, assuming that the infrared absorption follows a Lambert-Beer law, for a system containing just  and -phases, the relative amount of -PVDF, F(), can be calculated applying equation 1: It is to notice that the -phase content has been neglected in this calculation due to the small amount of this phase in the composite samples, as indicated by the corresponding band strength at 812 cm -1 in the FITR spectra of Figure 2. The error induced by this simplification will be within the 4% error estimated by the method itself [22]. It was observed that the presence of the BaTiO 3 nanoparticles promotes the crystallization of the -phase of the PVDF matrix, indicating that the ceramic filler act as a nucleating agent for this phase.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…Briefly, assuming that the infrared absorption follows a Lambert-Beer law, for a system containing just  and -phases, the relative amount of -PVDF, F(), can be calculated applying equation 1: It is to notice that the -phase content has been neglected in this calculation due to the small amount of this phase in the composite samples, as indicated by the corresponding band strength at 812 cm -1 in the FITR spectra of Figure 2. The error induced by this simplification will be within the 4% error estimated by the method itself [22]. It was observed that the presence of the BaTiO 3 nanoparticles promotes the crystallization of the -phase of the PVDF matrix, indicating that the ceramic filler act as a nucleating agent for this phase.…”
Section: Resultsmentioning
confidence: 85%
“…In all cases, the presence of β-phase can be observed through the presence of the absorption band at 840 cm -1 . In addition, the infrared spectra also reveal an absorption band at 812 cm -1 that also indicates the presence of small contents of -PVDF (figure 2) [22]. The -phase content present in each sample was calculated from the absorption bands at 764 and 840 cm -1 , characteristic of the  and -PVDF, respectively, with a procedure similar to the one reported in [19,20].…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Characteristic SEM images of the pristine polymer and the IL/polymer composites are represented in Figure 2 for both IL types, showing that for both IL types, the spherulitic microstructure characteristic of PVDF is observed [32]. (Figure 2d), the results being thus independent of the anion type.…”
Section: Morphological Variationsmentioning
confidence: 98%
“…4 shows variation of FTIR spectra with time for neat PVDF during isothermal crystallization at 150 1C and for the 20/80 blend and the dynamically vulcanized 20/80 blend at 120 1C in the region of 1000-550 cm À1 . These spectra show only a characteristic peaks (975, 795, 763, and 615 cm À1 ) of PVDF 20,[24][25][26][27][28][29][30] therefore blending and dynamic vulcanization does not induce the creation of polymorphic crystalline forms of PVDF. It seems that unlike nanofillers, a nano-scale phase separated structure cannot induce electroactive polymorphs in PVDF.…”
Section: Effects Of Dynamic Vulcanization and Isothermal Crystallizat...mentioning
confidence: 98%